Gender Equality in Housing Delivery - A Panacea to Adequate Housing Supply in Nigeria - Oriye, Olusegun; Owoeye, Oluranti; Weje, Innocent I. (Richtmann Publishing, 2012)
Women represent about fifty percent of the world’s population yet own less than one percent of the world’s property.Available literature reveals that housing has hitherto been seen as a male resource with women having access only to its useand content. A concept rooted in patriarchy and strengthened by societal norms. By this, women are usually not consulted duringthe various housing development processes. They are expected to adapt, even when they are major users and consumers ofhousing facilities and infrastructure. While the home-bound women devote 95.0% of their working hours to cleaning andmaintaining their environment, the working class and the female heads of households experience functional problems accessinghousing facilities and services in order to fulfill their socially and domestically accepted roles. In this regard, the major thrust ofthis research work is to review substantive and empirical evidences available in past literatures to set up a basis of suggestingthe conceptualization of women and housing as a distinct policy domain. Areas of focus in this paper therefore include housingdesign and planning, building materials production and supply, housing facilities and management. The paper recommends thatsince women have both ‘strategic’ and ‘political’ housing needs, the scope or rationale of women housing need should be treatedseparately from those of men’s or housing for all the poor.